The Relationship Between Body Mass Index and The Degree of Dementia in Elderly Patients with Memory Impairment at Memory Clinic Siloam Hospitals Lippo Village - Nathan Muliawan; Maurensia; Rocksy Fransisca Situmeang (Universitas Pelita Harapan, 2025)
Introduction: Body mass index (BMI) can describe the level of nutrition and vitality of a person. Monitoring BMI values prevents elderlies from various risks of disease, one of which is dementia. The development of neuropathological lesions in the olfactory bulb has been proposed to cause symptoms which affect dementia patients’ appetite and thus resulting in weight loss. Methods: A cross-sectional study was conducted among 55 memory impairment patients from ages ≥65 years at Siloam Hospitals Lippo Village Memory Clinic. Data was obtained using Montreal Cognitive Assessment – Indonesian Version (MoCA-INA) and Clinical Dementia Rating Scale (CDRS) and BMI was measured using Seca 703 instrument. Results: A significant relationship was found between body mass index and the degree of dementia with a value of p = 0.046 for MoCA examination and p = 0.039 for CDRS examination. The results of the analysis shows that underweight-normal (BMI <23kg/m2) patients have 3.8 times (95% CI 1.2-12.5) and 4.6 times (95% CI 1.2-17.0) the risk of having a moderate-severe degree respectively compared to overweight-obese (BMI ≥23kg/m2) patients. Conclusions: Lower late life BMI is related to higher degree of dementia